Why psychiatry needs an honest dose of gentle medicine - Cosgrove, Lisa; D'Ambrozio, Gianna; Herrawi, Farahdeba; Freeman, Moira; Shaughnessy, Allen (Frontiers in Psychiatry, 2023)
The pharmaceutical industry’s influence on psychiatric research and practice has been profound and has resulted in exaggerated claims of the effectiveness of psychotropic medications and an underreporting of harms. After the regulatory approval of fluoxetine, the pharmaceutical industry began promoting (and continues to promote) a chemical imbalance theory of emotional distress. In the last decade there has been an increased awareness about the limits of this theory and the risks of psychotropic medications. Nonetheless, the medicalization of distress, the sedimented belief in ‘magic bullets,’ and the push to ‘scale up’ mental health treatment has contributed to the meteoric rise in the prescription of psychiatric drugs and of polypharmacy. A major premise of this paper is that the conceptual framework of medical nihilism can help researchers and clinicians understand and address the harms incurred by inflated claims of the efficacy of psychotropic medications. We propose that psychiatry, and the mental health field more generally, adopt a model of ‘gentle medicine’ with regard to both the diagnosis of and treatment for mental health conditions and focus greater attention on the upstream causes of distress.